Timing of hospital admission in labour: latent versus active phase, mode of birth and intrapartum interventions. A correlational study. Issue 4 (August 2018) - Rota, A.; Antolini, L.; Colciago, E.; Nespoli, A.; Borrelli, S.E.; Fumagalli, S.
Abstract: Background: Hospitalization of women in latent labour often leads to a cascade of unnecessary intrapartum interventions, to avoid potential disadvantages the recommendation should be to stay at home to improve women's experience and perinatal outcomes. Aim: The primary aim of this study was to investigate the association between hospital admission diagnosis (latent vs active phase) and mode of birth. The secondary aim was to explore the relationship between hospital admission diagnosis, intrapartum intervention rates and maternal/neonatal outcomes. Methods: A correlational study was conducted in a large Italian maternity hospital. Data from January 2013 to December 2014 were collected from the hospital electronic records. 1.446 records of low risk women were selected. These were dichotomized into two groups based on admission diagnosis: 'latent phase' or 'active phase' of labour. Findings: 52.7% of women were admitted in active labour and 47.3% in the latent phase. Women in the latent phase group were more likely to experience a caesarean section or an instrumental birth, artificial rupture of membranes, oxytocin augmentation and epidural analgesia. Admission in the latent phase was associated with higher intrapartum interventions, which were statistically correlated to the mode of birth. Conclusions: Women admitted in the latent phase were more likely to experience intrapartum interventions, which increase the probability of caesarean section. Maternity services should be organized around women and families needs, providing early labour support, to enable women to feel reassured facilitating their admission in labour to avoid the cascade of intrapartum interventions which increases the risk of caesarean section.